2022
DOI: 10.1021/jacs.2c08838
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Design Principles to Elongate the Metal-to-Ligand Charge Transfer Excited-State Lifetimes of Square-Planar Nickel(II) Complexes

Abstract: Square-planar NiII complexes and their electronically excited states play key roles in cross-coupling catalysis and could offer new opportunities to complement well-known isoelectronic PtII luminophores. Metal-to-ligand charge transfer (MLCT) excited states and their deactivation pathways are particularly relevant in these contexts. We sought to extend the lifetimes of 3MLCT states in square-planar NiII complexes by creating coordination environments that seemed particularly well adapted to the 3d8 valence ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
40
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 38 publications
(46 citation statements)
references
References 154 publications
3
40
2
1
Order By: Relevance
“…184 Recent work demonstrated that when this structural distortion is made more difficult by suitable molecular design (Figure 9b), then longer MLCT lifetimes are achievable. 137 Many different research avenues are currently pursued with photoactive Ni II complexes, 183,185−187 and much remains to be discovered yet concerning the basic photophysics and photochemistry of square-planar 3d 8 complexes. Luminescent and photochemically exploitable MLCT excited states could be one of the future targets, and this challenge seems even greater than in the case of 3d 6 complexes.…”
Section: ■ Lessons Learned and Future Challengesmentioning
confidence: 99%
See 4 more Smart Citations
“…184 Recent work demonstrated that when this structural distortion is made more difficult by suitable molecular design (Figure 9b), then longer MLCT lifetimes are achievable. 137 Many different research avenues are currently pursued with photoactive Ni II complexes, 183,185−187 and much remains to be discovered yet concerning the basic photophysics and photochemistry of square-planar 3d 8 complexes. Luminescent and photochemically exploitable MLCT excited states could be one of the future targets, and this challenge seems even greater than in the case of 3d 6 complexes.…”
Section: ■ Lessons Learned and Future Challengesmentioning
confidence: 99%
“…Many different research avenues are currently pursued with photoactive Ni II complexes, , and much remains to be discovered yet concerning the basic photophysics and photochemistry of square-planar 3d 8 complexes. Luminescent and photochemically exploitable MLCT excited states could be one of the future targets, and this challenge seems even greater than in the case of 3d 6 complexes …”
Section: Parallels and Differences Between 3d6 And 3d10/3d8 Complexes...mentioning
confidence: 99%
See 3 more Smart Citations